HMGB1Modulates the Treg/Th17 Ratio in Atherosclerotic Patients - Tong, Xiao-hong; Zhou, Tian; Ding, Jia-wang; Wang, Xin-an; Luo, Cai-yun; Zheng, Xia-xia (Journal of Atherosclerosis and Thrombosis, 2016)
Aim: Atherosclerosis (AS) characterized as a chronic inflammatory disease. Multiple immune cells and inflammatory cytokines, such as high mobility group protein (HMGB1), regulatory T (Treg) cells, T helper (Th17) cells, and inflammation-related cytokines, play a key role in its pathophysiology. A large number of studies report that HMGB1 and Th17 cells may promote atherosclerosis progression, whereas Treg cells may play a protective role in atherosclerosis; thus, alterations in the Treg/Th17 ratio may exist in atherosclerosis diseases. Up till now, the relationships between HMGB1 levels and the Treg/Th17 ratio remain incompletely understood. The major purpose of this study was to investigate the relationship between HMGB1 levels and the Treg/Th17 ratio in patients with coronary artery atherosclerotic plaques. Methods: We enrolled patients with coronary atherosclerosis and normal coronary artery as the research subjects. Flow cytometry was used to analyze the Treg cells, the Th17 cells frequency, and the Treg/Th17 ratio. Otherwise, real-time polymerase chain reaction was used for assays the mRNA expressions of HMGB1, retinoic acid-related orphan nuclear receptor C (RORC), and forkhead-winged helix transcription factor (Foxp3). Moreover, enzyme-linked immunosorbent assays were used to detect the level of protein and cytokines, such as HMGB1, IL-10, TGF-β1, IL-17A, and IL-23. Results: Using flow cytometry, we observed a significantly increased of Th17 cell frequency, whereas Treg cell frequency significantly decreased in atherosclerotic patients. Consistently, the levels of RORC mRNA were significantly increased in coronary atherosclerosis (AS) group compared to normal coronary artery (NCA) group (P＜0.01). In contrast, the expression of Foxp3 mRNA was markedly lower in the AS group than in the NCA group (P＜0.01). Furthermore, we observed the serum concentrations of HMGB1, IL-17A, and IL-23 were significantly higher in the AS group than in the NCA group (P＜0.01, respectively), whereas the concentrations of serum IL-10 and TGF-β1 were significantly lower in the AS group than in the NCA group (P＜0.01, respectively). In addition, we also found that HMGB1 levels showed negative correlation with the Treg/Th17 ratio in the two groups (r=－0.6984, P＜0.01). Conclusions: The data in our study indicated that HMGB1 may promote atherosclerosis progression via modulating the imbalance in the Treg/Th17 ratio.